Evaluation of Pain Scale Decrease and Adverse Effects of Ketorolac Injections: An Observational Study in Patients with Postoperative Pain - Mawardi Ihsan; Fivy Kurniawati; Husna Khoirunnisa; Belladonna Chairini (Indonesian Journal of Pharmacy, 2019)
The use of ketorolac injections in Indonesia is restricted with the provision of 2-3 ampoules per day with a maximum of two days even though the literature states that ketorolac could be used for no more than five days. This study aimed to determine the decrease in pain scale as well as gastrointestinal and renal adverse effects of ketorolac injections in two days of use. This study was an observational study with one-group pre-test post-test design conducted prospectively. The group was a group of patients with postoperative pain who received ketorolac injections and were treated during January till April 2018 in an academic hospital in Yogyakarta. The results showed that ketorolac injections did not provide a statistically significant decrease in pain scale in two days of use compared to before surgery (median [range] = 2.0[0.0-9.33] vs 1.33[0.0-8.33]; p=0.32). Ketorolac injections decreased the kidney function of subjects in two days of use compared to before surgery based on creatinine values (0.76mg/dL vs 0.80mg/dL; p=0.024) and GFR (96.13mL/min/m2 vs 87.52mL/min/m2; p=0.023), and as many as 31 subjects (43.06%) experienced complaints that were suspected to be the gastrointestinal adverse effects of ketorolac injections with the three most complaints were bloating (18.06%), nausea (16.67%), and heartburn (15.28%). Those three results support the use of ketorolac injections following what has been regulated in the Indonesian National Formulary.